A study on usability of magnesium oxide with titanium dioxide in PVC door and window profiles - Kamisli, F; Turan, C (Elsevier Science Sa, 2005)
In this study, the usability of magnesium oxide with titanium dioxide used in the manufacture of polyvinyl chloride door and window profiles is investigated in terms of discoloration or fading and some mechanical properties. By each compound associated with the different amount of MgO and TiO2, five different compounds are used to produce PVC profiles of doors and windows. The most suitable profile in terms of discoloration is obtained from the compound containing MgO and TiO2 with the ratio of MgO to TiO2 of 1/3. It is observed that the addition of MgO into a compound dramatically decreases the elongation of material and thus, it improves the hardness of PVC-based material. It is concluded that the profiles fabricated from the compounds with the ratios of MgO to TiO2 of 1/2 and 1/1 do not meet the standard in terms of brittleness obtained from the impact strength testing in low temperature (-10degreesC). It is also concluded that although the brittleness of some profile associated with the ratios of MgO to TiO2 of 1/2 and 1/1 is not in standard values, the addition of the certain amount of MgO into the compound provides some improvements on the discoloration of PVC-based door and window profiles. The obtained results are evaluated by considering the previous studies and thus, they qualitatively agree with the previous studies. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: polyvinyl chloride panels; UV radiation; titanium dioxide